COLLECTIVE TRAUMA OF COLONIALISM IN SOUTHEAST ASIAN SHORT STORIES: A COMPARATIVE STUDY - Triono, Eko; Efendi, Anwar (Literature and Literacy, 2025)
Although colonial rule in Southeast Asia has formally ended, sociocultural and psychological wounds persist. If left unaddressed, this trauma can hinder efforts toward regional cohesion, cultural resilience, and sustainable development. This study examines the representation of collective trauma caused by colonialism in Southeast Asian short stories. It draws on Kai Erikson’s concept of collective trauma, postcolonial theory, and Claudio Guillén’s theory of comparative literature. The method employed is systematic content analysis with context-based inference. The primary texts analyzed include: Recuerdos de Patay by Caroline S. Hau (Philippines), Variola by Iksaka Banu (Indonesia), Victoria and Her Kimono by M. Shanmughalingam (Malaysia), and The Interview by Gopal Baratham (Singapore). Data collection was carried out through close reading, note-taking, and analytical observation. The data were analyzed qualitatively using content analysis. The findings reveal various dimensions of postcolonial collective trauma portrayed in the stories, including social disintegration, psychological dislocation, the erosion of communal bonds, intergenerational transmission of trauma, collective identity as victims, and transformations of meaning systems. These findings suggest that literature serves not only as a witness to historical wounds but also as a cultural space for negotiating memory, identity, and healing. In the Southeast Asian context, social healing is essential in shaping regional identity through the understanding of literature and culture.